2017
DOI: 10.1080/19420862.2017.1304869
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane TNF-dependent uptake of anti-TNF antibodies

Abstract: TNF-α (TNF), a pro-inflammatory cytokine is synthesized as a 26 kDa protein, anchors in the plasma membrane as transmembrane TNF (TmTNF), and is subjected to proteolysis by the TNF-α converting enzyme (TACE) to release the 15 kDa form of soluble TNF (sTNF). TmTNF and sTNF interact with 2 distinct receptors, TNF-R1 (p55) and TNF-R2 (p75), to mediate the multiple biologic effects of TNF described to date. Several anti-TNF biologics that bind to both forms of TNF and block their interactions with the TNF receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 62 publications
4
55
0
1
Order By: Relevance
“…In our observations, the reactive epitope in the scFvcontaining bispecific antibodies was the scFv portion. It remains to be determined whether the high immunogenic potential of the scFv was inherently due to its sequence or structure, or whether the IgG may have played a role by causing the internalization of the scFv by antigen-presenting cells, 16 or whether it was a synergistic combination of the two factors. The latter hypothesis is supported by the discovery that a potentially large number of healthy treatment-naïve individuals produce pre-existing human anti-V H antibodies (HAVH).…”
Section: Discussionmentioning
confidence: 99%
“…In our observations, the reactive epitope in the scFvcontaining bispecific antibodies was the scFv portion. It remains to be determined whether the high immunogenic potential of the scFv was inherently due to its sequence or structure, or whether the IgG may have played a role by causing the internalization of the scFv by antigen-presenting cells, 16 or whether it was a synergistic combination of the two factors. The latter hypothesis is supported by the discovery that a potentially large number of healthy treatment-naïve individuals produce pre-existing human anti-V H antibodies (HAVH).…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly a consequence of the interaction between anti-TNF and tmTNF on antigen presenting cells and the subsequent rapid internalization. The internalized anti-TNF will be processed and its peptides displayed on the surface of the APCs will mount a T cell proliferation response [285]. Unfortunately, technical factors, standardization of the assays used to determine ADAs, and the timing of the measurements makes this a complex subject to investigate.…”
Section: Clinical Responsementioning
confidence: 99%
“…mTNF-α, however, interacts primarily with TNFR2 (both soluble and transmembrane forms) and mediates effects that are overlapping and contrary to those of sTNF-α ( 7 , 11 ). Notably, the crosstalk between mTNF-α and TNFR2 triggers bi-directional signaling in target cells and mTNF-α-expressing cells ( 12 14 ). Increasing evidence has shown that in the tumor microenvironment, the interaction between mTNF-α and TNFR2 plays a significant role in tumor progression ( 15 ).…”
mentioning
confidence: 99%